La Politique Balkanique de la France au Cours du XXème Siècle - Catsiapis, Jean (Études helléniques / Hellenic Studies, 2002)
Throughout the twentieth century, French policy in the Balkans was based on a large and strong Serbia in an effort to limit the influence of Austria and Hungary, ally of France’s main enemy, Germany. Greece was the second pillar of the French policy. In fact the French had been ‘monitoring’ Greece since the Treaty of London, signed May 7, 1832. However, in the last decade of the twentieth century, Paris had to accept the disintegration of Yugoslavia plus the fact that France now exercised a mere economic rather than political influence on Greece. Moreover that influence depends on the overall economic climate.